THE IMPLEMENTATION OF TOTAL PHYSICAL RESPONSE METHOD IN LEARNING ENGLISH AT TK KHAIRUL IMAM MEDAN - Aulia Sofiea Putri; Andang Suhendi (Universitas Islam Sumatera Utara, 2023)
This research is aimed at finding and describing how Total Physical Response (TPR) method can improve the ability of students at TK Khairul Imam Medan in learning English. The application of English for early childhood is not an easy thing. Therefore, it is necessary to use methods so that early childhood can better understand the meaning of the English language. One of the methods probably used is TPR method. It aims to make English easier to understand by early children. This research was conducted with the aim of knowing the results of the implementation of the Total Physical Response (TPR) Method in early childhood English learning. This study uses a qualitative descriptive field research method. The research location is at the TK Khairul Imam. The research subjects include the head of the kindergarten and the teacher. Data obtained through interviews, observation, and documentation. The results of this study describe the implementation of TPR method in early childhood English learning carried out in the school. This study shows the role of the teacher and the stages of English learning activities with the TPR method in the school.